PECULIARITIES OF FOOD SAFETY MANAGEMENT SYSTEM WHEN PRODUCING TURBIDITY STABLE BEVERAGES - Sergeeva I.Y.; Permyakova L.V. (Техника и технология пищевых производств)
To produce high quality products at modern enterprises of food industry it is necessary to establish effective systems of quality and safety such as HACCP. The paper presents a brief review of modern quality management systems of food products. This study deals with peculiarities of food safety management system when producing beverages stable to turbidity. Improvement of the system is considered in the framework of one of the principles of the concept of quality of beverages prone to turbidity. Implementation is performed by augmenting the implemented safety management system of the production process with additive critical control points. The quantitative content of the turbidity components of beverages is controlled with the designation of critical limits of their concentration and, actually, a processing aid in the technological chain. The necessity of additive critical control points at the stage of beer fermentation has been established. The HACCP worksheet for stable beer has been developed. Regarding the storage and preparation of chitosan the production program of mandatory preliminary actions when producing stable beer using chitosan has been proposed.